Advances in the Use of Thin, Spray-on Liner Systems - James F. Archibald (Canadian Institute of Mining, Metallurgy and Petroleum, 2002)
In historic mining practice, typical thin liner support systems have been considered to comprise non-reinforced or mesh-reinforced shocrete linings. In the early 1990?s, development of alternate forms of liner systems was initiated in Canada which is now undergoing significant international growth in countries which sustain major mining activity. Now internationally designated as thin, spray-on liner systems, a wide spectrum of liner materials, ranging from liquid/liquid to liquid/solid component combinations, has become commercially available. This innovative family of products is characteristically identified as being rapidly deployable, capable of creating ultra-fast setting coverage over rock surfaces, and able to develop tenacious adhesion and pull strength capacities for resisting rock falls and movements. This paper presents a summary of current liner developments and use in principal mining districts world wide. Additionally, a database of material properties for principal product types used in mining and a review of common quality control testing procedures under development are provided. Such information is based upon recent Canadian and international efforts being taken to assess and develop user standards for the implementation of thin, spray-on liners as rock support in mines. This work is intended to continue for a period of years, with the eventual goal being to establish support and installation guidelines for mines based on quantifiable laboratory and field research.